Extraction and characterization of polysaccharides from Semen Cassiae by microwave-assisted aqueous two-phase extraction coupled with spectroscopy and HPLC. (25th June 2016) - Chen, Zhi; Zhang, Wei; Tang, Xunyou; Fan, Huajun; Xie, Xiujuan; Wan, Qiang; Wu, Xuehao; Tang, James Z.
Highlights: MAATPE combined with microwave-assisted extraction and aqueous two-phase extraction in one-step procedure. MAATPE conditions for simultaneous extraction of different polysaccharides from Semen Cassiae was investigated. Extraction efficiency of MAATPE were higher than heating solvent extraction and ultrasonic assisted extraction. Polysaccharides from both phases were characterized by FT-IR and hydrolysis prior to derivative HPLC. Two polysaccharides extracted by MAATPE had the dissimilar compositions of monosaccharides. Abstract: A novel and rapid method for simultaneous extraction and separation of the different polysaccharides from Semen Cassiae (SC) was developed by microwave-assisted aqueous two-phase extraction (MAATPE) in a one-step procedure. Using ethanol/ammonium sulfate system as a multiphase solvent, the effects of MAATPE on the extraction of polysaccharides from SC such as the composition of the ATPS, extraction time, temperature and solvent-to-material ratio were investigated by UV–vis analysis. Under the optimum conditions, the yields of polysaccharides were 4.49% for the top phase, 8.80% for the bottom phase and 13.29% for total polysaccharides, respectively. Compared with heating solvent extraction and ultrasonic assisted extraction, MAATPE exhibited the higher extraction yields in shorter time. Fourier-transform infrared spectra showed that two polysaccharides extracted from SC to the top and bottom phases by MAATPE were different from each other in their chemical structures. Through acid hydrolysis and PMP derivatization prior to HPLC, analytical results by indicated that a polysaccharide of the top phases was a relatively homogeneous homepolysaccharide composed of dominant gucose glucose while that of the bottom phase was a water-soluble heteropolysaccharide with multiple components of glucose, xylose, arabinose, galactose, mannose and glucuronic acid. Molar ratios of monosaccharides were 95.13:4.27:0.60 of glucose: arabinose: galactose for the polysaccharide from the top phase and 62.96:14.07:6.67: 6.67:5.19:4.44 of glucose: xylose: arabinose: galactose: mannose: glucuronic acid for that from the bottom phase, respectively. The mechanism for MAATPE process was also discussed in detail. MAATPE with the aid of microwave and the selectivity of the ATPS not only improved yields of the extraction, but also obtained a variety of polysaccharides. Hence, it was proved as a green, efficient and promising alternative to simultaneous extraction of polysaccharides from SC.